DEVELOPMENT OF SOIL HYDROLOGICAL, PHYSICAL, AND CHEMICAL PROPERTIES AFTER SUCCESSION IN BURNED PEAT FORESTS IN CENTRAL KALIMANTAN - Abdi, Aditya
Peat soil is a type of soil that is formed due to the accumulation of organic material such as fallen leaves, tree remains, grass and animal bodies that rot in the soil after thousands of years. Peat soil has hydrological, physical and chemical characteristics that are very unique compared to soil in general, which is related to its contribution in maintaining environmental stability, especially as its role as carbon storage and carbon sequestration. Disturbances experienced by peat in Central Kalimantan, such as land conversion, climate change (El-Nino), and drainage damage the condition of peat soil from hydrological, physical and chemical aspects, thereby changing the role of peat from storing carbon to being a source of carbon emissions. Therefore, the aim of this research is to analyze the development of hydrological, physical and chemical properties of peat soil on different sites based on different post-fire succession ages by comparing with unburned peat forests or RA (reference area). Data collected in the field included peat depth, water table, and soil samples. Hydrological, physical, and chemical properties of soil samples collected were analyzed at Laboratorium UPR Terpadu. Hydrological properties analyzed included Water Holding Capacity (WHC) and Water Content (WC), physical properties were bulk density, and chemical properties included organic matter content, C-Organic content, N-Total, pH, and Phosphate (PO4) concentration. The results showed that fire certainly has an impact on soil characteristics where improvement due to succession for 26 years (EF-1997) was able to improve soil quality so that it was similar to RA, while EF-2015 (7 years) was similar but still not similar in the value of water holding capacity, and soil pH.